Stress State of Gas-Saturated Massif with Moveable Free Surface - A.A. Kushunin; V.A. Savenkov (Механика машин, механизмов и материалов, 2009)
This paper deals with results of modeling and examination of mechanic and mathematic model of gas-saturated massif with moveable free surface.